Simple non-invasive analysis of embryonic stem cell-derived cardiomyocytes beating in vitro - Radaszkiewicz, Katarzyna Anna; Sýkorová, Dominika; Karas, Pavel; Kudová, Jana; Kohút, Lukáš; Binó, Lucia; Večeřa, Josef; Víteček, Jan; Kubala, Lukáš; Pacherník, Jiří (The Review of scientific instruments, 2016)
The analysis of digital video output enables the non-invasive screening of various active biological processes. For the monitoring and computing of the beating parameters of cardiomyocytes in vitro, CB Analyser (cardiomyocyte beating analyser) software was developed. This software is based on image analysis of the video recording of beating cardiomyocytes. CB Analyser was tested using cardiomyocytes derived from mouse embryonic stem cells at different stages of cardiomyogenesis. We observed that during differentiation (from day 18), the beat peak width decreased, which corresponded to the increased speed of an individual pulse. However, the beating frequency did not change. Further, the effects of epinephrine modulating mature cardiomyocyte functions were tested to validate the CB Analyser analysis. In conclusion, data show that CB Analyser is a useful tool for evaluating the functions of both developing and mature cardiomyocytes under various conditions in vitro.
Keywords: Cell Line; videomikroskopie; myší embryonální kmenové buňky; Mouse Embryonic Stem Cells; Image Processing, Computer-Assisted; Software; Microscopy, Video; adrenalin; Myocardial Contraction; Epinephrine; počítačové zpracování obrazu; kardiomyocyty; Animals; zvířata; Myocytes, Cardiac; myši; buněčné linie; kontrakce myokardu; software; Mice